Variation control affecting construction works for Lembaga Kemajuan Tanah Persekutuan(FELDA) - Mohd. Yunus, Nurul Ayun (2007)
Variation means alteration, change or modification of design, quality or quantity of work omission, addition or substitution of the work including the alteration of the kind or standard of any of the materials or goods to be used in the work, and the removal from site of any work, materials or goods which are not in accordance in the contract. The aim is of this study research is to covering the initial planning, while works is in progress and until the completion of works to minimize the need for variation works right from the start . The method of this study involved literature review, interview and based on the case study and the analysis by qualitative method. The process of data collection involved obtaining primary data from the literature review and the secondary data was generated from the case study. From the analysis of this study type and factors influence to variation; problem that influence and the implication to variation; and the strategy action can be taken to minimize the variation were identified. In conclusion, the strategy action that can be taken were identified to minimize or control the variation works during planning stage until construction stage.